How do you divide ( -i+1) / (2i +10 )i+12i+10 in trigonometric form?

1 Answer
Apr 6, 2018

(-i+1)/(2i+10) =1/2(2/13 - i3/13)i+12i+10=12(213i313)

Explanation:

A complex number zz is of the form

z=a+biz=a+bi

We define the Polar coordinates of zz to be (r,theta)(r,θ), as seen in the image below.

![http://mathonweb.com/help_ebook/html/complex_2.htm](useruploads.socratic.org)

From this diagram we get some more properties:

r=sqrt(a^2+b^2)r=a2+b2

sin theta = b/r => b=rsinthetasinθ=brb=rsinθ
costheta=a/r =>a=rcosthetacosθ=ara=rcosθ

If we substitute bb and aa into the definition of a complex number, we have

z=rcostheta+irsintheta = r(costheta+isintheta)z=rcosθ+irsinθ=r(cosθ+isinθ)

Our trigonometric sum resembles color(red)("Euler's identity")Euler's identity:

e^(icolor(red)alpha)=coscolor(red)alpha+isincolor(Red)(alphaeiα=cosα+isinα

Thus,

z=re^(itheta)z=reiθ

In our case, it'd be easier to write them in this exponential form then transform it into trigonometric form.

Let color(blue)(z_1 = -i+1z1=i+1 and color(blue)(z_2 = 2i+10z2=2i+10.

We do not need to find theta_1θ1 and theta_2θ2 now, so we will let them as that.

r_1 = sqrt(a_1^2+b_1^2) = sqrt(1^2+(-1)^2) = sqrt2r1=a21+b21=12+(1)2=2
r_2 = sqrt(a_2^2+b_2^2)=sqrt(100+4)=sqrt(104)=2sqrt(26)r2=a22+b22=100+4=104=226

:. z_1/z_2=(r_1e^(itheta_1))/(r_2e^(itheta_2))

z_1/z_2 = sqrt2/(2sqrt26) * e^(i(theta_1-theta_2)

z_1/z_2 = 1/(2sqrt13) * e^(i(theta_1-theta_2)

We can still apply Euler's identity to e^(i(theta_1-theta_2)). We have:

e^(i(theta_1-theta_2)) = cos(theta_1-theta_2)+isin(theta_1-theta_2)

The color(blue)("Difference formula") for cosine and sine is, as follows:

cos(a-b)=cosacosb+sinasinb
sin(a-b) = sinacosb-cosasinb

cos(theta_1 - theta_2) = costheta_1costheta_2+sintheta_1sintheta_2
sin(theta_1-theta_2) = sintheta_1costheta_2-costheta_1sintheta_2

From the properties we got earlier, we know:

costheta_1 = 1/sqrt2
sintheta_1 = -1/sqrt2

costheta_2 = 5/sqrt26
sintheta_2=1/sqrt26

After we calculate the values we needed, we reach this:

cos(theta_1-theta_2) = 2/sqrt13
sin(theta_1-theta_2)= -3/sqrt13

Finally, we get:

z_1/z_2 = 1/(2sqrt13) (2/sqrt13 -i3/sqrt13)

z_1/z_2 = 1/2(2/13 - i3/13)

:.

(-i+1)/(2i+10) =1/2(2/13 - i3/13)